Challenges of Teaching Social Studies in Overcrowded Classrooms - Teachers' Perspective in Second Cycle of Basic Education in Independent Zakho Administration - Nida Fattah (RaSAIL Media Group, Semarang, Indonesia, 2026)
This study aimed to identify the challenges of teaching social studies in overcrowded classrooms from the perspective of teachers in the second cycle of basic education in Independent Zakho Administration according to the following variables: gender, years of teaching experience, and grade level. The study sample included 87 male and female social studies teachers from Grades 5-6. A questionnaire consisting of 25 items was developed based on relevant literature and distributed to the research sample during October 2025. The study found statistically significant differences at the 0.05 level between the means of sample responses according to gender and years of experience variables, indicating that overcrowded classrooms significantly impact teaching effectiveness differently based on these demographic factors. However, no statistically significant differences were found regarding the grade level taught or the interaction between gender and years of experience. Based on these findings, the researcher recommended several measures, most importantly the need for educational authorities to develop policies to reduce class sizes, provide additional classroom facilities, and offer specialized training programs for teachers to manage large classes effectively.